ASSESSMENT OF ECOSYSTEM SERVICES IN THE ARDVI VILLAGE (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The importance of assessing ecosystem services (ES) via case study of Ardvi settlement stems from an unprecedented increase in global, regional, and local interest towards the evaluation and valuation of various ecosystem services. A comprehensive assessment and valuation of the diverse and numerous ES (provisioning, regulating, cultural, and supporting) in Armenia's ecosystems is essential for sustainable resource management, the latter's multifunctional use, and effective conservation. The assessment of ecosystem services is a crucial step in developing the ES concept for decision-making and management. The need for this assessment of ES by the example of the Ardvi Village is also driven by targeted actions initiated since 2011 by the government and various organizations in Armenia. These actions aim to demonstrate the value of ES for a small village and illustrate how this value can be integrated into spatial and community development planning.
Keywords: ecosystem services; comprehensive geographic assessment; carbon dioxide